35q^(-3/5)=-21q^(-8/5)-((-21q^8/5)*35q^(-3/5))

Re-arrange and solve for q. I did it but got some mad answer.

Printable View

- May 9th 2008, 07:25 AMjdizzle1985Re-arranging and solving for q
35q^(-3/5)=-21q^(-8/5)-((-21q^8/5)*35q^(-3/5))

Re-arrange and solve for q. I did it but got some mad answer. - May 9th 2008, 09:19 AMmasters
How 'bout showing us how far you got!

- May 9th 2008, 10:50 AMMoo
Hello,

Let's put it all in one side :

$\displaystyle 35q^{-3/5}+21q^{-8/5}+({\color{red}(-21q^{8/5})*35q^{-3/5}})=0$

Look at the red thing

$\displaystyle -21q^{8/5}*35q^{-3/5}=-(21*35)q^{8/5-3/5}=-21*35 q^1=-21 \cdot 35 \cdot q$

Hence the equation is now :

$\displaystyle 35q^{-3/5}+21q^{-8/5}-21 \cdot 35 \cdot q=0$

Multiplying everything by $\displaystyle q^{8/5}$, we get :

$\displaystyle 35q^1+21q^0-21\cdot 35 \cdot q^{13/5}=0$

$\displaystyle 35q+21-21\cdot 35 \cdot q^{13/5}=0$

I got mad answers too (Nerd) - May 9th 2008, 11:38 AMblair_alane